'It's now or never'—nulliparous women's experiences of pregnancy at advanced maternal age: A grounded theory study. (January 2019) - Southby, Clara; Cooke, Alison; Lavender, Tina
Abstract: Background: Delayed pregnancy is increasingly common in many countries including the UK. There has been international interest in providing maternity care which aims to improve outcomes for mothers and babies when pregnancy occurs after the age of 35. Despite this, there is a lack of understanding of the experience of pregnancy at advanced maternal age from the woman's perspective. Objectives: To explore the experience of uncomplicated pregnancy for nulliparous women aged 35 and over and determine key processes involved in their pregnancy journey. Design: A two phase constructivist grounded theory study. Setting: South West of England, United Kingdom. Participants: 15 nulliparous women aged 35 and over, in their third trimester of pregnancy. Methods: Data were collected through semi-structured, in depth interviews which were transcribed and analysed using coding, constant comparison and memo-writing. Results: The core category 'It's now or never' reflects how women may experience their pregnancy. This appears to influence feelings of readiness to become a mother, anxieties about the pregnancy and their care choices. This was felt more acutely as maternal age advances towards 40 years and beyond. Conclusions: Women's understanding that their future chances to have a baby may be limited can impact upon the way pregnancy is experienced. Despite having an uncomplicated pregnancy, older pregnant women may experience considerable worry throughout their pregnancy. Further research is required on how health care providers can better support women in early pregnancy and in making decisions regarding childbirth choices which are related to age.